The Impact of Audit Market Concentration on Audit Quality: Evidence from Australia - Alismail, Faisal (Curtin University, 2023)
This study examines the impact of audit market concentration on audit quality in Australia. The hypotheses are developed within an agency theory framework and tested using data collected from publicly listed Australian firms for the period from 2010 to 2018. The results of this study suggest that audit market concentration is positively associated with audit quality.